How corporate social responsibility initiatives in social media affect awareness and customer engagement - Loureiro, S. M. C.; Lopes, J. (Journal of Promotion Management, 2019)
The aim of this study is to explore if organizations that engage stakeholders in social media with co-creative approaches (allowing them to be active participants and decision-makers in their online corporate social responsibility (CSR) activities) can be more effective in building awareness, increasing stakeholders’ empowerment and participation levels, than firms who use the conventional design and communication of these activities, where the stakeholder has no participation in the process and is merely taken as a passive agent. Thus, a real online participatory CSR initiative is examined through an online questionnaire, which gathered 322 valid responses. Results provide evidence that co-creating socially responsible activities in social media can increase not only the awareness for such actions, but also increase empowerment, participation levels, positive word-of-mouth dissemination, and reinforce consumer-brand ties in the process.